2016
DOI: 10.2174/1874210601610010505
|View full text |Cite
|
Sign up to set email alerts
|

Surface Roughness of Initial Enamel Caries Lesions in Human Teeth After Resin Infiltration

Abstract: Background:Low viscosity resin infiltration of initial caries lesions is a modern microinvasive method to treat initial cries lesions. However, only scarce information is available about the long-term surface alterations of infiltrated lesions.Methods:Twenty-eight premolar teeth exhibiting non-cavitated initial caries lesions (International Caries Detection and Assessment System (ICDAS code 1&2)) were divided into two groups, one of which was infiltrated with resin, and the other remained untreated. The teeth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 34 publications
4
18
0
Order By: Relevance
“…34 Ourcolor results came in agreement with those of Bak et al 25 and Yetkiner et al 35 who proved the ability of resin infiltrant to resist thermal and discoloration challenges. Regarding surface roughness, our results agreed with previous studies [36][37][38][39][40] which concluded that resin infiltration of enamel lesions can provide and maintain smoother surface. However, these results contrast those of other researches [41][42][43] which reported that surface roughness and color stability of resin-infiltrated enamel lesions were less than ideal and could further recede with aging in the oral environment.…”
Section: Discussionsupporting
confidence: 91%
“…34 Ourcolor results came in agreement with those of Bak et al 25 and Yetkiner et al 35 who proved the ability of resin infiltrant to resist thermal and discoloration challenges. Regarding surface roughness, our results agreed with previous studies [36][37][38][39][40] which concluded that resin infiltration of enamel lesions can provide and maintain smoother surface. However, these results contrast those of other researches [41][42][43] which reported that surface roughness and color stability of resin-infiltrated enamel lesions were less than ideal and could further recede with aging in the oral environment.…”
Section: Discussionsupporting
confidence: 91%
“…The increased surface roughness observed on the resin-infiltrated lesions with aging in the present study, may be attributed to internal and thermal stresses generated by water sorption and thermal expansion and contraction. 19 The present results agreed with former studies [30][31][32] which reported the ability of resin infiltrants to provide and maintain smoother enamel surface. However, other studies 19,33,34 came in contrast, as they reported that surface roughness of resin-treated enamel lesions were not ideal and might further recede with aging.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, internal infiltration obviously should be the first step, and occlusion of the tiny pores might even be enhanced by applying active pressure with the aid of packable composite resins prior to polymerization [75]. The infiltrant resin used in the present investigation (Icon Caries Infiltrant; DMG) has been shown to be compatible to generally utilized adhesive restorations [32,76], and does not impair the shear bond strengths to dentin [77], while adhesion to sound [78][79][80] or demineralized [40,78,80,81] enamel even was increased (if compared to other adhesive systems); moreover, tensile bond strength testing was accompanied by a high portion of mixed (cohesive in enamel) failures [80], thus indicating a strong and reliable enamel hybrid layer composed of resin tags enveloping the enamel crystallites [82]. These aspects obviously indicate that final composite resin restorations can be bonded adhesively to the resin-infiltrated hard substances, and this should result in stable repairs, thus complying with the concepts of minimum intervention dentistry [1,2], and solving (or at least minimizing) some of the clinical problems discussed above.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous papers have clarified that both the tendency of surface breakdown [33,34] and the ICDAS codes [35,36] will increase with advanced radiographic lesion extensions. Due to the material's inherent mechanical properties [37], the infiltration approach using an unfilled and low-viscosity resin will not be able to completely fill up any (micro-)cavitations [2,3,38], nor will it be able to adequately smoothen the infiltrated surface of demineralized (and rough) enamel [39]; thus, several investigations have clearly elucidated that roughness of infiltrated lesions will remain increased if compared to sound enamel [18,20,21,25,40], and this will not be perfectible by various polishing procedures [41]. Rough surfaces (with R a values exceeding 0.2 μm as the critical threshold), however, are susceptible to facilitate biofilm accumulation, and this has been revealed for infiltrated surfaces as well, even if to a lesser extent if compared to non-infiltrated lesions [17,19,42].…”
Section: Introductionmentioning
confidence: 99%